Meningkatkan Hasil Belajar Pendidikan Agama Katolik dengan Menerapkan Metode Pembelajaran Demonstrasi Berpasangan Siswa Kelas VI SD Negeri 38 Mataram - Santoso, Demetrius Herbasuki Budi (TSAQOFAH, 2021)
This study aims: To find out the application of the Paired Demonstration learning method in Improving Learning Outcomes of Catholic Religious Education for Class VI students of SD Negeri 38 Mataram in the 2020/2021 academic year; To find out the increase in learning outcomes of Catholic Religious Education with the Paired Demonstration Learning Method for Class VI students of SD Negeri 38 Mataram in the 2020/2021 academic year. This research was designed using Classroom Action Research. The subjects in this study were 8th graders of SD Negeri 38 Mataram, consisting of 2 female students and 6 male students. While the research procedure goes through the stages of planning, implementing actions, observing, and reflecting. The results showed that: Learning by applying the paired demonstration learning method can improve the learning outcomes of Catholic Religious Education for Class VI students at SD Negeri 38 Mataram, which is marked by an increase in student learning outcomes in each cycle, namely in the pre-cycle average of 80.25; the average of the first cycle was 85.38 and the second cycle was 90.25. Learning by applying the paired demonstration learning method can improve the classical learning outcomes of Catholic Religious Education for Class VI students at SD Negeri 38 Mataram which is marked by an increase in student learning outcomes in each cycle, namely; 62.50% ; 87.50% ; 100%.